Using Stable Isotopes to Infer the Impacts of Habitat Change on the Diets and Vertical Stratification of Frugivorous Bats in Madagascar - Reuter, Kim E.; Wills, Abigail R.; Lee, Raymond W.; Cordes, Erik E.; Sewall, Brent J. (PLOS ONE, 2016)
Human-modified habitats are expanding rapidly; many tropical countries have highly fragmented and degraded forests. Preserving biodiversity in these areas involves protecting species–like frugivorous bats–that are important to forest regeneration. Fruit bats provide critical ecosystem services including seed dispersal, but studies of how their diets are affected by habitat change have often been rather localized. This study used stable isotope analyses (δ15N and δ13C measurement) to examine how two fruit bat species in Madagascar, Pteropus rufus (n = 138) and Eidolon dupreanum (n = 52) are impacted by habitat change across a large spatial scale. Limited data for Rousettus madagascariensis are also presented. Our results indicated that the three species had broadly overlapping diets. Differences in diet were nonetheless detectable between P. rufus and E. dupreanum, and these diets shifted when they co-occurred, suggesting resource partitioning across habitats and vertical strata within the canopy to avoid competition. Changes in diet were correlated with a decrease in forest cover, though at a larger spatial scale in P. rufus than in E. dupreanum. These results suggest fruit bat species exhibit differing responses to habitat change, highlight the threats fruit bats face from habitat change, and clarify the spatial scales at which conservation efforts could be implemented.